Bridging the gap between the short and the long run in macroeconomics: outline of the GSMS-SS model of economic growth and the business cycle - Mueller, Antony Peter (2014)
The GSMS-SS model shows under which conditions credit-driven economic expansions are unsustainable and how such booms revert into busts. If central banks pursue a policy of inflation targeting and prevent deflation from happening when technological progress would lower the price level, they instigate an unsustainable boom and face malicious deflation in the bust phase of the business cycle instead of benign deflation that would have come without intervention. Credit-based economic expansions can go on when accompanied by technological progress. Yet when the pace of productivity gains lags behind monetary expansion, the boom reverts into deflationary contraction. The model links the concept of natural production frontier to steady state of the standard economic growth model with exogenous technological progress and demonstrates how expansive monetary and fiscal policy provokes a boom bust cycle when it moves the economy beyond its steady state.